DETEKSI DINI PENYAKIT DIABETES MELITUS - Venti Agustina; Marlenita Irma Tekege; Fanisa Carolin; Arum Dewi Wulandari; Apianus Weya; Oltry Gritly Chreyna Lampongajo (Universitas Kristen Satya Wacana Salatiga, 2021)
The increasing number of people with type 2 Diabetes Mellitus is a global health threat. Of course, the prevalence rate of diabetes mellitus must be prevented with both preventive and promotive actions. One form of prevention that can be sought is by detecting as early as possible in people who have risk factors. Therefore, this community service activity is carried out to detect the risk of diabetes mellitus, by checking blood sugar levels when measuring BMI and abdominal circumference which are indicators of diabetes mellitus. The results of the examination of 21 people (12 women, 9 men) showed the following results 13 people had blood glucose level (GDS) > 200 mg/dl, and 8 people had blood glucose level (GDS) < 200 mg/dl, 13 people with abdominal circumference > 80 cm (women) and 8 people with abdominal circumference > 90 cm (men), 13 people were categorized as overweight (BMI > 25kg/m2). The results above show that there are still many people who are not aware that they are at risk of developing DM, so there needs to be regular checks and health education about DM problems.